Molecular phylogenetics and diversity of the Himalayan shrew ( Soriculus nigrescens Gray, 1842) (Eulipotyphla, Soricidae) in Southwest China - Jiang, Haijun; Fu, Changkun; Tang, Keyi; Li, Fengjun; Faiz, Abu Ul Hassan; Guo, Keji; Liu, Shaoying; Chen, Shunde (Zootaxa, 2023)
The Himalayan shrew, Soriculus nigrescens Gray, 1842, belongs to the monotypic genus Soriculus, which is distributed mainly in the Himalayan region. Previous authors have studied its classification based on morphological and molecular data. However, no comprehensive study of the diversity and phylogeny of this species has been performed. In this study, we investigated the molecular phylogeny, genetic diversity, and species divergence of S. nigrescens based on one mitochondrial gene and three nuclear genes. A total of 124 samples from 27 sites in Southwest China were analyzed. Our molecular phylogenetic analyses and species divergence reveal non-monophyly of Soriculus, potentially representing two genera and three clades. Populations from Yunnan (Clade YN) represent the subspecies S. n. minors and should recover the full species status. Populations from Himalayas (Clade A) represent the species S. nigrescens, while populations from southeastern Nyenchen Tanglha Mountains and southern Himalayas (Clade B) represent a new cryptic and unnamed species. Species delimitation analyses and deep genetic distance analysis clearly support the species status of these three evolving clades. The putative new genus and cryptic species should be studied and identified in the future using a more extensive sampling combined with a comprehensive morphological and phylogenetic analysis.